2019
DOI: 10.1155/2019/9416381
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry Results of Formed Osteodefects When Using Nanocrystalline CeO2 in the Early Stages of Regeneration

Abstract: This paper studies of the use of nanocrystalline cerium dioxide with artificially formed bone tissue defects. The results of morphometry confirmed the antialterative effect in the early stages of the reparative process of damaged bone tissue. When using calcium hydroxide with nanodispersed cerium dioxide, the nature of osteogenesis should be characterized as activated. In case of damage to the dentin of the roots of the teeth, dentinogenesis in presence of CeO2 occurs with the formation of a combined dentin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This is why the medicine is called "smart" and makes CeO 2 a promising agent for use in nanomedicine [30][31][32][33][34][35]. In particular, it allows one to stabilize the wound environment to neutralize reactive oxygen species or any other free radicals, providing antioxidant, antibacterial, and anti-inflammatory effects [1,26,[35][36][37]. The effect of electron transfer can be repeated many times as the wound discharge penetrates through the polysaccharide hydrogel structure directly to the CeO 2 nanoparticles, or if the wound flora changes.…”
Section: Introductionmentioning
confidence: 99%
“…This is why the medicine is called "smart" and makes CeO 2 a promising agent for use in nanomedicine [30][31][32][33][34][35]. In particular, it allows one to stabilize the wound environment to neutralize reactive oxygen species or any other free radicals, providing antioxidant, antibacterial, and anti-inflammatory effects [1,26,[35][36][37]. The effect of electron transfer can be repeated many times as the wound discharge penetrates through the polysaccharide hydrogel structure directly to the CeO 2 nanoparticles, or if the wound flora changes.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension of calcium hydroxide was used as the control. This assay showed that nanocrystalline CeO 2 could improve osteogenesis and decrease inflammatory response [169].…”
Section: Cerium Dioxide Nanoparticlesmentioning
confidence: 92%
“… 76 Nanocrystalline CeO 2 promotes dentinogenesis in the damaged teeth root. 209 All aforementioned osteogenic properties of cerium‐doped innovative nanomaterials indicate the potential applications of cerium in bone tissue engineering and implantology.…”
Section: Application Of Re Smart Nano‐biomaterials In Bone Tissue Engineeringmentioning
confidence: 99%